Low viscosity papermaking grade cmc for heat transfer paper and process for its preparation
Patent Information
- Application Number
- CN202611214132.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
现有热升华转移纸用低粘度造纸级CMC依然存在纯度、热稳定性、水溶溶失率、热升华转印率和染料吸附率较差的问题
本发明提供了一种热升华转移纸用低粘度造纸级CMC及其制备工艺,本发明通过以下方法同时提高了热升华转移纸用低粘度造纸级CMC的纯度、热稳定性、水溶溶失率、热升华转印率和染料吸附率。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a low-viscosity paper-grade CMC for thermal sublimation transfer paper and its preparation process. Background Technology
[0002] Sublimation transfer paper is a core consumable in digital sublimation printing, widely used in textiles, apparel, home décor, and advertising signage. With the widespread adoption of high-speed digital printing technology, higher demands are placed on the coating smoothness, transfer clarity, and environmental adaptability of the transfer paper coating. Sodium carboxymethyl cellulose (CMC), as the main film-forming aid in the sublimation transfer paper coating, directly determines the final quality of the transfer paper.
[0003] However, in practical engineering applications, existing low-viscosity paper-grade CMC for thermal sublimation transfer paper still has the following performance shortcomings: First, due to excessive degradation of the molecular chain, the water solubility of low-viscosity CMC decreases sharply, making the coating prone to moisture absorption, stickiness, and wrinkling during high-temperature and high-humidity transfer, resulting in smudging of the transferred pattern; Second, the sodium chloroacetate hydrolysis side reaction in the carboxymethylation process is severe, resulting in high levels of byproducts such as sodium glycolate and chloride, which not only reduces film strength but also decomposes during high-temperature transfer, producing an irritating odor and contaminating the substrate being transferred; Third, the initial decomposition temperature of low-viscosity CMC is mostly below 280℃, and it is prone to slight thermal degradation at transfer temperatures of 180-220℃, leading to color deviation and darkening of the transferred pattern, which cannot meet the requirements of long-term continuous high-speed transfer; Fourth, the dye adsorption rate is relatively high, and it is easy to form hydrogen bonds with disperse dyes, resulting in insufficient dye sublimation and release, with the transfer rate generally below 95%, which increases dye costs and affects the color saturation of the pattern. Therefore, the overall performance of existing low-viscosity paper-grade CMC for sublimation transfer paper, including purity, thermal stability, water solubility loss rate, sublimation transfer rate, and dye adsorption rate, still needs to be systematically improved. Summary of the Invention
[0004] The purpose of this invention is to provide a low-viscosity paper-grade CMC for thermal sublimation transfer paper and its preparation process, thereby solving the following technical problems: The existing low-viscosity paper-grade CMC used in sublimation transfer paper still suffers from problems such as poor purity, thermal stability, water solubility loss rate, sublimation transfer rate, and dye adsorption rate.
[0005] The objective of this invention can be achieved through the following technical solutions: A process for preparing low-viscosity paper-grade CMC for thermal sublimation transfer paper includes the following steps: S1: Add cotton linter cellulose to an ethanol aqueous solution and stir for 15-20 min. Then add sodium hydroxide aqueous solution dropwise and keep it at 35℃ for 80 min for alkalization. Then raise the temperature to 45-48℃, then add hydrogen peroxide aqueous solution dropwise and stir for 20-30 min. Then add sodium chloroacetate in batches and react at 52-54℃ for 120 min. After cooling to 30℃, adjust the pH to 7.0-7.3. Finally, filter under reduced pressure, wash the filter cake, dry, pulverize and sieve to obtain low viscosity CMC powder. S2: Add low-viscosity CMC powder to an ethanol-water solution and stir at 25-40℃ for 20-40 min. Then adjust the pH to 8.2-8.6, stir for 10 min, add ethylene glycol diglycidyl ether, stir for 30 min, raise the temperature to 50-52℃ and keep it at that temperature for crosslinking for 2.5-3.5 h. After cooling to 30℃, adjust the pH to 7.0-7.3, then filter under reduced pressure, wash the precipitate, dry, pulverize, and sieve to obtain low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0006] Preferably, the mass ratio of cotton linter cellulose, ethanol aqueous solution, sodium hydroxide aqueous solution, hydrogen peroxide aqueous solution, and sodium chloroacetate in S1 is 100:450:300:5-8:120.
[0007] Preferably, the mass fraction of the ethanol aqueous solution in S1 is 90%.
[0008] Preferably, the sodium hydroxide aqueous solution in S1 has a mass fraction of 30%.
[0009] Preferably, the mass fraction of the hydrogen peroxide aqueous solution in S1 is 30%.
[0010] Preferably, the sodium chloroacetate in S1 needs to be added in three equal batches, with each batch spaced 20-25 minutes apart.
[0011] Preferably, the mass ratio of the ethanol aqueous solution, low viscosity CMC powder, and ethylene glycol diglycidyl ether in S2 is 1500:100:2.5-3.
[0012] Preferably, the mass fraction of the ethanol aqueous solution in S2 is 75%.
[0013] Preferably, during the thermal insulation and crosslinking process described in S2, the pH needs to be monitored every 30 minutes and maintained at 8.0-8.5.
[0014] The beneficial effects of this invention are: This invention provides a low-viscosity paper-grade CMC for sublimation transfer paper and its preparation process. This invention simultaneously improves the purity, thermal stability, water solubility loss rate, sublimation transfer rate, and dye adsorption rate of the low-viscosity paper-grade CMC for sublimation transfer paper through the following methods.
[0015] (1) The present invention employs a process of alkalization at 35°C for 80 minutes, which allows the amorphous regions of cotton linter cellulose to swell sufficiently, significantly reducing crystallinity and providing uniform and accessible reaction sites for subsequent oxidative degradation and carboxymethylation reactions. If the alkalization temperature is higher than 40°C, it will cause premature thermal degradation and peeling reactions of cellulose molecular chains, resulting in a wider molecular weight distribution; if the alkalization time is less than 60 minutes, the amorphous regions will not swell sufficiently, the reaction sites will be unevenly distributed, and the final product will have a large degree of substitution dispersion and poor batch stability.
[0016] (2) The hydrogen peroxide added in this invention decomposes under alkaline conditions to generate hydroxyl radicals, which can selectively cleave the β-1,4 glycosidic bonds in the cellulose molecular chain. This allows for controlled degradation and precise control of the molecular weight, thereby achieving precise adjustment of low viscosity. Since cellulose has a two-phase structure with alternating crystalline and amorphous regions, only the amorphous region swells fully after alkalization, while the glycosidic bonds in the crystalline region are tightly bound and difficult for free radicals to penetrate. Therefore, the degradation reaction preferentially occurs at the weak points in the amorphous region. In this invention, oxidative degradation is performed before carboxymethylation. At this time, cellulose is in a heterogeneous swollen state of alkali cellulose, and hydroxyl radicals can effectively contact the glycosidic bonds in the amorphous region, resulting in high degradation efficiency and good controllability. Lower molecular weights can be obtained with the same amount of hydrogen peroxide, and the molecular weight distribution of the product is narrower. A uniform molecular weight distribution is beneficial for the uniform progress of the subsequent carboxymethylation reaction. If oxidative degradation is performed after carboxymethylation, three drawbacks arise: First, the carboxymethyl groups introduced by carboxymethylation create significant steric hindrance, hindering free radicals from approaching the main chain glycosidic bonds; second, the carboxyl groups react with hydroxyl radicals, and the self-quenching effect between free radicals intensifies, leading to a significant decrease in the effective degradation agent concentration; third, the degradation reaction preferentially occurs in molecular chain segments with higher substitution degrees, further broadening the molecular weight distribution. Ultimately, this results in a significantly increased product viscosity at the same degradation agent dosage, easy formation of gel particles during dissolution, and poor film uniformity.
[0017] (3) The present invention adopts a three-batch, intermittent feeding method for sodium chloroacetate, which effectively avoids the instantaneous local high concentration of sodium chloroacetate in the system, maintains a uniform alkaline reaction environment, and significantly inhibits the alkaline hydrolysis side reaction of sodium chloroacetate (generating sodium glycolate). This not only improves the reaction efficiency and raw material utilization rate, but also reduces the content of by-products and improves the purity of the product. The uniform degree of substitution distribution makes it less likely for "fish eyes" to appear when the product dissolves, and at the same time provides uniform reaction sites for subsequent cross-linking reactions. The carboxymethylation reaction temperature of 52-54℃, which matches the batch feeding, precisely balances the rates of the main reaction and the side reaction: it ensures that the carboxymethylation reaction can quickly reach the target degree of substitution of 0.6-0.7, and avoids the intensification of sodium chloroacetate hydrolysis, the thermal degradation of alkali cellulose and the increase in the peeling reaction rate due to excessive temperature, thus preventing the increase of by-products, excessive degradation of molecular chains and widening of molecular weight distribution. This invention strictly controls the degree of substitution within a narrow range of 0.6-0.7, achieving an optimal balance between hydrophilicity and application performance: if the degree of substitution is below 0.6, the molecular chain is not hydrophilic enough, the dissolution rate is slow, the solution viscosity is unstable, and cracks are easily generated due to internal stress after film formation; if the degree of substitution is above 0.7, the molecular chain is too hydrophilic, the film water retention rate is too high, the dye and water molecules are too strongly bound during the transfer process and are difficult to sublimate and release, and at the same time the water solubility loss rate of the coating decreases, making it easy to absorb moisture and become sticky after transfer.
[0018] (4) The two epoxy groups in the ethylene glycol diglycidyl ether molecule added in this invention will preferentially undergo ring-opening reaction with the hydroxyl groups on the CMC molecular chain under weakly alkaline conditions (a small amount reacts with the carboxyl groups), forming covalent bridges between different molecular chains and constructing a mild three-dimensional network structure. This invention achieves a good synergistic effect between crosslinking modification and early hydrogen peroxide degradation by precisely controlling the amount of crosslinking agent, reaction temperature, and pH value: low molecular weight CMC molecular chains have more ends, requiring a higher density of crosslinking points to form a continuous network; at the same time, low molecular weight CMC has higher swelling degree and better molecular chain mobility in ethanol medium, and the crosslinking efficiency is significantly improved compared with medium and high molecular weight CMC. The mild three-dimensional network constructed by appropriate crosslinking can significantly improve the water solubility loss rate, avoiding the coating from dissolving in water under high temperature and high humidity transfer conditions; at the same time, it can improve the wet tensile strength, enabling the transfer paper to withstand the mechanical tension during high-speed coating and transfer processes; in addition, it can also increase the initial thermal decomposition temperature to above 290℃, ensuring that the coating is stable and does not decompose at a transfer temperature of 180-220℃. If the amount of crosslinking agent is insufficient, an effective three-dimensional network cannot be formed, the film will dissolve immediately upon contact with water, and the water loss rate will increase significantly, completely failing to meet the water resistance requirements of thermal sublimation transfer paper. If the crosslinking agent is excessive, an overly dense network structure will be formed, resulting in restricted molecular chain movement, brittle film, and a significant reduction in water retention. The coating will dry too quickly, easily leading to pinhole defects, and gel particles will also be generated in the solution, affecting coating uniformity. This invention controls the crosslinking reaction at 50-52℃ and pH 8.0-8.5. These process conditions avoid both insufficient crosslinking due to excessively low temperatures and excessively high temperatures that lead to excessively rapid reaction rates, localized over-crosslinking, and the formation of gel particles. Simultaneously, it prevents the slight degradation of CMC molecular chains caused by high temperatures, thus avoiding the offsetting effect of viscosity improvement brought about by crosslinking.
[0019] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. The embodiments described below are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1: The preparation process of a low-viscosity paper-grade CMC for thermal sublimation transfer paper is as follows: S1: After crushing cotton linter cellulose and passing it through a 40-mesh standard sieve, take 100g and add it to 450g of a 90% ethanol aqueous solution and stir for 15min. Then, add 300g of a 30% sodium hydroxide aqueous solution at 10g / min and keep it at 35℃ for alkalization for 80min. Then, raise the temperature to 45℃, and then add 5g of a 30% hydrogen peroxide aqueous solution at 0.4g / min while stirring at 200r / min and stirring for 20min. Then, add 120g of sodium chloroacetate in three equal batches, with each batch 20min apart. After the addition is complete, add 5g of sodium chloroacetate. The reaction was carried out at 2℃ for 120 min (with the degree of carboxymethylation controlled at 0.6-0.7). After cooling to 30℃, glacial acetic acid was added at 0.5 g / min while stirring at 600 r / min to adjust the pH to 7.0. The mixture was then filtered under reduced pressure and soaked and washed with 200 g of 70% ethanol aqueous solution for 15 min. The filter cake was then filtered again and washed 4 times (until no white silver chloride precipitate was produced when a small amount of filtrate was added to a silver nitrate solution acidified with dilute nitric acid). Finally, the mixture was vacuum dried at 60℃ and -0.09 MPa for 12 h, pulverized, and passed through a 100-mesh standard sieve to obtain low-viscosity CMC powder. S2: Add 100g of low-viscosity CMC powder to 1500g of 75% ethanol aqueous solution and stir at 25℃ for 20min. Then adjust the pH of the filtrate to 8.2 with 10% sodium hydroxide aqueous solution and stir for 10min. Then add 2.5g of ethylene glycol diglycidyl ether at 0.2g / min while stirring at 150r / min. Stir for 30min, then raise the temperature to 50℃ and keep it at that temperature for 2.5h (the pH needs to be monitored every 30min during this period and maintained at a certain level). 8.0-8.5 (add sodium hydroxide aqueous solution if necessary), cool to 30℃ and adjust pH to 7.0 with glacial acetic acid, then filter under reduced pressure and wash the precipitate three times repeatedly with 500mL of 70% ethanol aqueous solution (until no white precipitate is found when silver nitrate solution acidified with dilute nitric acid is added to the final washing liquid, and the pH is neutral after rinsing with pure water). Finally, vacuum dry at 60℃ and -0.09MPa for 8h, pulverize, and pass through a 100-mesh sieve to obtain low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0022] Example 2: The preparation process of a low-viscosity paper-grade CMC for thermal sublimation transfer paper is as follows: S1: After crushing cotton linter cellulose and passing it through a 40-mesh standard sieve, take 100g and add it to 450g of a 90% ethanol aqueous solution and stir for 18min. Then, add 300g of a 30% sodium hydroxide aqueous solution dropwise at 10g / min and keep it at 35℃ for alkalization for 80min. Then, raise the temperature to 47℃, and then add 6.5g of a 30% hydrogen peroxide aqueous solution dropwise at 0.4g / min while stirring at 200r / min and stirring for 25min. Then, add 120g of sodium chloroacetate in three equal batches, with each batch 23min apart. After the addition is complete, The reaction was carried out at 53℃ for 120 min (with the degree of carboxymethylation controlled at 0.6-0.7). After cooling to 30℃, glacial acetic acid was added at 0.5 g / min while stirring at 600 r / min to adjust the pH to 7.2. The mixture was then filtered under reduced pressure and soaked in 200 g of 70% ethanol aqueous solution. The filter cake was washed with stirring for 15 min and then filtered again. The washing was repeated 5 times (until no white silver chloride precipitate was produced when a small amount of filtrate was added to a silver nitrate solution acidified with dilute nitric acid). Finally, the mixture was vacuum dried at 60℃ and -0.09 MPa for 12 h, pulverized, and passed through a 100-mesh standard sieve to obtain low-viscosity CMC powder. S2: Add 100g of low-viscosity CMC powder to 1500g of 75% ethanol aqueous solution and stir at 33℃ for 30min. Then adjust the pH of the filtrate to 8.4 with 10% sodium hydroxide aqueous solution and stir for 10min. Then add 2.7g of ethylene glycol diglycidyl ether at 0.2g / min while stirring at 180r / min and stirring for 30min. Raise the temperature to 51℃ and keep it at that temperature for 3h (the pH needs to be monitored every 30min and maintained at 8). The pH was adjusted to 7.2 with glacial acetic acid after cooling to 30°C (add sodium hydroxide aqueous solution if necessary). Then, the precipitate was filtered under reduced pressure and washed repeatedly 4 times with 500 mL of 70% ethanol aqueous solution (until no white precipitate was found after adding dilute nitric acid-acidified silver nitrate solution to the final washing liquid, and the pH was neutral after rinsing with pure water). Finally, the precipitate was vacuum dried at 60°C and -0.09 MPa for 9 hours, pulverized, and passed through a 100-mesh sieve to obtain low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0023] Example 3: The preparation process of a low-viscosity paper-grade CMC for thermal sublimation transfer paper is as follows: S1: After crushing cotton linter cellulose and passing it through a 40-mesh standard sieve, take 100g and add it to 450g of a 90% ethanol aqueous solution and stir for 20min. Then, add 300g of a 30% sodium hydroxide aqueous solution at 10g / min and keep it at 35℃ for alkalization for 80min. Then, raise the temperature to 48℃, and then add 8g of a 30% hydrogen peroxide aqueous solution at 0.4g / min while stirring at 200r / min and stirring for 30min. Then, add 120g of sodium chloroacetate in three equal batches, with each batch 25min apart. After the addition is complete, heat the solution at 54℃. The reaction was carried out at ℃ for 120 min (controlling the degree of carboxymethylation substitution to 0.6-0.7). After cooling to 30℃, glacial acetic acid was added at 0.5 g / min while stirring at 600 r / min to adjust the pH to 7.3. The mixture was then filtered under reduced pressure and soaked in 200 g of 70% ethanol aqueous solution. The filter cake was washed with stirring for 15 min and then filtered again. The washing was repeated 5 times (until no white silver chloride precipitate was produced when a small amount of filtrate was added to a silver nitrate solution acidified with dilute nitric acid). Finally, the mixture was vacuum dried at 60℃ and -0.09 MPa for 12 h, pulverized, and passed through a 100-mesh standard sieve to obtain low-viscosity CMC powder. S2: Add 100g of low-viscosity CMC powder to 1500g of 75% ethanol aqueous solution and stir at 40℃ for 40min. Then adjust the pH of the filtrate to 8.6 with 10% sodium hydroxide aqueous solution and stir for 10min. Then add 3g of ethylene glycol diglycidyl ether at 0.2g / min while stirring at 200r / min. Stir for 30min and then raise the temperature to 52℃ and keep it at 3.5h (the pH needs to be monitored every 30min and maintained at 8). The pH was adjusted to 7.3 with glacial acetic acid after cooling to 30°C (0-8.5, with sodium hydroxide aqueous solution added if necessary). Then, the precipitate was filtered under reduced pressure and washed repeatedly four times with 500 mL of 70% ethanol aqueous solution (until no white precipitate was found after adding dilute nitric acid-acidified silver nitrate solution to the final washing liquid, and the pH was neutral after rinsing with pure water). Finally, the precipitate was vacuum dried at 60°C and -0.09 MPa for 10 hours, pulverized, and passed through a 100-mesh sieve to obtain low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0024] Comparative Example 1: Compared with Example 1, this comparative example only omits the step of "adding 5g of 30% hydrogen peroxide aqueous solution at 0.4g / min while stirring at 200r / min and stirring for 20min" during the preparation process of S1. All other steps and parameters are the same, and will not be repeated here. The final result is low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0025] Comparative Example 2: Compared with Example 1, this comparative example differs only in that the step in the preparation process of S1, "reheating to 45°C, then adding 5g of 30% hydrogen peroxide aqueous solution at 0.4g / min while stirring at 200r / min and stirring for 20min, then adding 120g of sodium chloroacetate in three equal batches with a 20min interval between each batch, and reacting at 52°C for 120min (controlling the degree of carboxymethylation substitution to 0.6-0.7)," is replaced with "then adding 120g of sodium chloroacetate in three equal batches with a 20min interval between each batch, reacting at 52°C for 120min (controlling the degree of carboxymethylation substitution to 0.6-0.7), then cooling to 45°C, then adding 5g of 30% hydrogen peroxide aqueous solution at 0.4g / min while stirring at 200r / min and stirring for 20min." All other steps and parameters are the same, and will not be repeated in this comparative example. The final result is low-viscosity paper-grade CMC for thermal sublimation transfer paper.
[0026] Comparative Example 3: Compared with Example 1, this comparative example only replaces the step in the preparation process of S1, which is "then add 120g of sodium chloroacetate in three batches with an interval of 20min between each batch, and react at 52°C for 120min after the addition is complete", with "then add 120g of sodium chloroacetate all at once and react at 52°C for 120min". All other steps and parameters are the same, and will not be repeated in this comparative example. The final result is low viscosity paper grade CMC for thermal sublimation transfer paper.
[0027] Comparative Example 4: Compared with Example 1, this comparative example only replaces the step in the preparation process of S1, which is "then add 120g of sodium chloroacetate in three equal batches, with an interval of 20min between each batch, and react at 52°C for 120min after the addition is completed", with "then add 120g of sodium chloroacetate in three equal batches, with an interval of 20min between each batch, and react at 65°C for 120min after the addition is completed". All other steps and parameters are the same, and will not be repeated in this comparative example. The final result is low viscosity paper grade CMC for thermal sublimation transfer paper.
[0028] Comparative Example 5: Compared with Example 1, this comparative example only replaces the step in the preparation process of S1, which is "then add 120g of sodium chloroacetate in three equal batches, with an interval of 20min between each batch, and react at 52°C for 120min after the addition (controlling the degree of carboxymethylation substitution to 0.6-0.7)", with "then add 120g of sodium chloroacetate in two equal batches, with an interval of 20min between each batch, and react at 65°C for 120min after the addition (controlling the degree of carboxymethylation substitution to 0.8-0.9)". All other steps and parameters are the same, and will not be repeated in this comparative example. The final result is low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0029] Comparative Example 6: Compared with Example 1, this comparative example only omits the processing in S2. The low-viscosity CMC powder prepared in S1 is directly used as the low-viscosity papermaking grade CMC for thermal sublimation transfer paper. All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, the low-viscosity papermaking grade CMC for thermal sublimation transfer paper is obtained.
[0030] Comparative Example 7: Compared with Example 1, this comparative example only replaces "2.5g ethylene glycol diglycidyl ether" added during the S2 preparation process with "8g ethylene glycol diglycidyl ether". All other steps and parameters are the same, and will not be repeated in this comparative example. The final result is low viscosity paper grade CMC for thermal sublimation transfer paper.
[0031] Comparative Example 8: Compared with Example 1, this comparative example only replaces "stirring for 30 minutes, then heating to 50°C and holding for 2.5 hours" in the S2 preparation process with "stirring for 30 minutes, then heating to 60°C and holding for 2.5 hours". All other steps and parameters are the same, and will not be repeated in this comparative example. The final result is low-viscosity paper grade CMC for thermal sublimation transfer paper.
[0032] Performance testing: 5g of low-viscosity paper-grade CMC for thermal sublimation transfer paper, prepared in each example and comparative example, was added to 95g of deionized water. The mixture was stirred at 300r / min for 60min at 35℃, followed by vacuum degassing at -0.08MPa for 30min. The solution was then poured into a horizontally placed polytetrafluoroethylene mold (dimensions: 150mm×150mm×5mm), and the solution thickness was controlled to be 2.0±0.1mm (final dry film thickness approximately 0.1mm). Surface air bubbles were gently scraped off with a glass rod. The film was then naturally dried at 25℃ and 50%RH for 24h, followed by vacuum drying at 40℃ and -0.08MPa for 12h. Finally, the film was peeled off the mold and placed in a standard environment at 23℃ and 50%RH for 48h to adjust its condition, yielding a low-viscosity paper-grade CMC sample for thermal sublimation transfer paper. This film preparation method is suitable for both fully crosslinked and non-crosslinked CMC samples. After immersion and dissolution of the non-crosslinked sample, the residual solids can be collected to complete the water solubility loss rate test.
[0033] (1) Physicochemical and mechanical properties ① Viscosity determination: Referring to GB 1886.232-2016 standard, 2g of low-viscosity paper-grade CMC for thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention was added to 98.0g of deionized water, and stirred at 25°C for 30min. The viscosity (mPa·s) of the solution was measured using a Brookfield rotational viscometer with rotor No. 1 at a rotation speed of 60r / min. The measurement results are shown in Table 1. ② Purity determination: Referring to GB 1886.232-2016 standard, the sodium glycolate content (A1) and chloride content (A2) in the low-viscosity paper grade CMC prepared in Examples 1-3 and Comparative Examples 1-8 of this invention were determined. Simultaneously, the loss on drying (A3) after drying at 105°C for 4 hours was determined. Then, the purity (%) of sodium carboxymethyl cellulose was calculated using the difference method according to the following formula: Purity (%) = 100% - A1 - A2 - A3 The measurement results are shown in Table 1; ③ Determination of tensile strength: Referring to GB / T 1040.3-2006 standard, the low-viscosity paper grade CMC samples of the thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention were cut into Type 2 dumbbell-shaped test samples (gauge length 50 mm, width 10 mm, total length 150 mm). Then, under the conditions of 23℃ and 50%RH, the tensile strength (MPa) at a tensile speed of 50 mm / min and a clamp spacing of 100 mm was measured. The test results are shown in Table 1. ④ Test of abrasion resistance: The low-viscosity paper grade CMC samples of the thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention were cut into 100mm×100mm test samples. After weighing, the samples were subjected to 100 revolutions with a CS-10 rubber grinding wheel under a load of 500g and a rotation speed of 60r / min. Then, the abrasive on the surface of the samples was removed with a soft brush and weighed. The corresponding mass loss (mg) was then calculated. The test results are shown in Table 1. Table 1: Statistical Table of Physical, Chemical and Mechanical Properties Test Data
[0034] (2) Sublimation transfer rate, dye adsorption rate, water solubility loss rate, water retention rate, and thermal stability ① Determination of thermal sublimation transfer rate: Referring to Appendix B of T / ZZB 1950-2020, the sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention was formulated into a 10% aqueous solution using low-viscosity paper-grade CMC and coated onto the base paper, with the dry coating weight controlled at 10 ± 1 g / m². 2 After drying, a transfer paper sample was obtained. Then, a 100% magenta block was printed onto the transfer paper sample using a digital printer. Finally, a flatbed transfer machine was used to transfer the sample to 100% polyester plain weave fabric (150 g / m²) at 200°C and 0.3 MPa pressure for 30 seconds. 3 After conditioning the paper to a standard environment for 24 hours, the color density (D1) of the transfer paper before transfer and the color density (D2) of the residual transfer paper after transfer were measured using an X-Rite 528 reflectance densitometer (D65 light source, 2° viewing angle). The corresponding sublimation transfer rate was then calculated according to the following formula: Sublimation transfer rate (%) = [1 - D2 / D1] × 100% The measurement results are shown in Table 2; ② Determination of dye adsorption rate: 0.100 g of the thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention was added to 50 mL of a 100 mg / L Reactive Brilliant Red X-3B aqueous solution. The solution was stirred at 150 r / min for 24 h at 25 °C (until adsorption equilibrium). The supernatant was then collected, and the absorbance was measured at 538 nm using a UV-Vis spectrophotometer. The dye concentration (mg / L) in the solution after adsorption equilibrium was calculated, and the corresponding dye adsorption rate was calculated according to the following formula: Dye adsorption rate (%) = (initial dye concentration - dye concentration in solution after adsorption equilibrium) / initial dye concentration × 100%; the measurement results are shown in Table 2; ③ Determination of water solubility loss rate: The thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention was cut into 50mm×50mm square test samples using low-viscosity paper-grade CMC samples, dried at 105℃ to constant weight, and the dry film mass m0 was recorded. After weighing, the sample was completely immersed in a sealed beaker containing 200 mL of 25°C deionized water and soaked at a constant temperature for 24 hours. After soaking, the undissolved intact film residue was removed, and the surface free small molecules were gently rinsed with deionized water. The sample was then vacuum dried at 60°C until constant weight, and the mass of the residual film was recorded as m1. The water solubility loss rate was calculated according to the following formula: Water solubility loss rate (%) = [(m0-m1) / m0] × 100% The measurement results are shown in Table 2; ④ Determination of water retention rate: 2g of the thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention were added to 98.0g of deionized water with low-viscosity paper-grade CMC and stirred at 25°C for 30min to fully swell and form a hydrogel. 10g of the gel was accurately weighed and placed in a centrifuge tube with a quantitative filter paper at the bottom. The tube was centrifuged at 3000rpm for 15min to separate the free water. The free water was discarded, and the total mass W1 of the residual gel in the centrifuge tube was weighed. An equal amount of 10g of the original gel was dried to constant weight to obtain the dry CMC mass W0 within the gel. The water retention rate was calculated according to the following formula: Water retention rate (%) = [(W1-W0) / W1] × 100% The measurement results are shown in Table 2; ⑤ Determination of thermal stability: Referring to GB / T 27761-2011 standard, the initial decomposition temperature (temperature at which mass loss is 5%) of the 10 mg low viscosity paper grade CMC for thermal sublimation transfer paper prepared in Examples 1-3 and Comparative Examples 1-8 of this invention was determined using a simultaneous thermal analyzer (TG-DSC) under a nitrogen atmosphere with a flow rate of 50 mL / min and a heating rate of 10 °C / min, from 25 °C to 600 °C. The results are shown in Table 2. Table 2: Statistical Table of Test Data for Transfer Application, Water Resistance, Water Retention and Thermal Stability
[0035] Data Analysis: As can be seen from Tables 1 and 2, the low-viscosity paper-grade CMC for sublimation transfer paper prepared in the embodiments of the present invention has excellent purity, thermal stability, tensile strength, water solubility loss rate, abrasion resistance, water retention, sublimation transfer rate and dye adsorption rate.
[0036] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.
Claims
1. A process for preparing low-viscosity paper-grade CMC for thermal sublimation transfer paper, characterized in that, Includes the following steps: S1: Add cotton linter cellulose to an ethanol aqueous solution and stir for 15-20 min. Then add sodium hydroxide aqueous solution dropwise and keep it at 35℃ for 80 min for alkalization. Then raise the temperature to 45-48℃, then add hydrogen peroxide aqueous solution dropwise and stir for 20-30 min. Then add sodium chloroacetate in batches and react at 52-54℃ for 120 min. After cooling to 30℃, adjust the pH to 7.0-7.
3. After post-processing, low viscosity CMC powder is obtained. S2: Add low-viscosity CMC powder to an ethanol-water solution and stir at 25-40℃ for 20-40 min. Then adjust the pH to 8.2-8.6, stir for 10 min, add ethylene glycol diglycidyl ether, stir for 30 min, raise the temperature to 50-52℃ and keep it at that temperature for crosslinking for 2.5-3.5 h. After cooling to 30℃, adjust the pH to 7.0-7.
3. After post-treatment, low-viscosity paper-grade CMC for thermal sublimation transfer paper is obtained.
2. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The mass ratio of cotton linter cellulose, ethanol aqueous solution, sodium hydroxide aqueous solution, hydrogen peroxide aqueous solution, and sodium chloroacetate in S1 is 100:450:300:5-8:
120.
3. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The ethanol aqueous solution in S1 has a mass fraction of 90%.
4. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The sodium hydroxide aqueous solution described in S1 has a mass fraction of 30%.
5. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The mass fraction of the hydrogen peroxide aqueous solution described in S1 is 30%.
6. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The sodium chloroacetate described in S1 needs to be added in three equal batches, with each batch spaced 20-25 minutes apart.
7. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The mass ratio of the ethanol aqueous solution, low viscosity CMC powder, and ethylene glycol diglycidyl ether in S2 is 1500:100:2.5-3.
8. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, The mass fraction of the ethanol aqueous solution in S2 is 75%.
9. The preparation process of low-viscosity paper-grade CMC for thermal sublimation transfer paper according to claim 1, characterized in that, During the thermal insulation and crosslinking process described in S2, the pH needs to be monitored every 30 minutes and maintained at 8.0-8.
5.
10. A low-viscosity paper-grade CMC for thermal sublimation transfer paper, characterized in that, It is made by the preparation process described in any one of claims 1-9.
